Leucocytoclastic vasculitis in a patient with COVID-19 with positive SARS-CoV-2 PCR in skin biopsy. Issue 10 (29th October 2020) - Camprodon Gómez, Maria; González-Cruz, Carlos; Ferrer, Berta; Barberá, María Jesús
Abstract : Main skin manifestations of COVID-19 have been recently classified. However, little is known about cutaneous histopathological patterns and the presence of SARS-CoV-2 in these skin lesions. We present a healthy 29-year-old man who developed a leucocytoclastic vasculitis for COVID-19 with positive SARS-CoV-2 PCR in skin biopsy.